Panduan Praktek Klinis dan Clinical Pathway Sebagai Solusi Efisiensi Pembiayaan Diagnosa Hernia Inguinalis, Appendisitis, dan Sectio Caesarea di RSI Gondanglegi - Farida Rozany; Navis Yuliansyah; Siti J Susilo (Universitas Muhammadiyah Yogyakarta, 2017)
Aim of this study are to describing factors inefficient in health insurance program in RSI Gondanglegi especially for operatif procedure. This research was conducted with descriptive analysis method. Starting with the observation in the medical record at diagnosis in the case above, and compare with form details the cost of the patients in the period from the first quarter of 2016. The results obtained financing on medical services and medicines. By making the policy of medical services and medicines for patients health insurance, standards of clinical care, effective communication of team with related units, and an increase in the type of hospital grade is expected to improve the efficiency of implementation in RSIG.